MODEL PENYIARAN PESAN DAKWAH ISLAM DI MEDIA DIGITAL: STUDI PUSTAKA ATAS TEORI KOMUNIKASI, DAKWAH, DAN MEDIA BARU - Ash Shiddieqy, Muhammad Dicky Hasbi; Amrifin, Haerul (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2025)
The rapid development of digital media over the past two decades has dramatically transformed the landscape of disseminating religious messages, including Islamic da’wah. Da’wah content now spans various digital platforms, ranging from social media, online video channels, and podcasts to applications based on artificial intelligence, enabling it to reach beyond geographical boundaries that were previously unattainable through conventional da’wah methods.Despite its vast potential, there is still no comprehensive model of digital da’wah broadcasting that is firmly grounded in an integrated framework of communication theory, da’wah studies, and new media theory. This study aims to develop a conceptual model for disseminating Islamic da’wah messages in digital media through a systematic literature review that integrates these three theoretical frameworks.The methodology employed is a systematic literature review of scholarly books published in the last five years, as well as accredited national journals and reputable international journals published within the last three years. The findings indicate that an effective model for digital da’wah broadcasting must encompass four main synergistic components: contextually adaptive message construction, media selection based on the characteristics of digital audiences, interactivity strategies that encourage active engagement from mad’u (audiences), and continuous evaluation and feedback mechanisms.This model is formulated as the Integrative Digital Da’wah Model, which can serve as a framework for practitioners and academics in the fields of da’wah studies and Islamic communication